Synthesis and characterization of Cu(II)-pyrazole complexes for possible anticancer agents; conformational studies as well as compatible in-silico and in-vitro assays - Enas Aljuhani (Elsevier, 2021)
New pyrazole derivatives were prepared and used to synthesize new bioactive agents from Cu(II) complexes that have OSN donors. Analytical and spectral (IR, UV-Vis, MS, 1H NMR, ESR & XRD) instruments characterized these complexes as well as their corresponding ligands. The bonding mode has been modified from ligand to ligand and the molar ratio for isolated complexes has also varied (1:1/1:2, M:L). The geometry of isolated complexes was commonly proposed, based on electronic transitions and ESR spectral-parameters. Via computational approaches, these structures were optimized using standard programs (Gaussian 09 & HyperChem 8.1) under the required basis set. Consequently, important physical characteristics have been obtained after finishing the optimization process. Inhibition behavior of all new synthesizes was studied by MOE module as in-silico approach which conducted versus the crystal structure of NUDT5 protein (6gru) of breast cancer cells. The interaction features summarized from docking processes, reveal effective inhibition validity for new Cu(II) complexes versus breast cancer cells. This according to scoring energy values and the stability of docking complexes in true interaction path (bond length ≤3.5 Å) particularly with Cu(II)-L3 and Cu(II)-L4 complexes. This reflects the possibility of successful behavior during practical application through in-vitro assay that intended in this study. Finally, the degree of toxicity of such new compounds to the breast cancer cell line was determined by in-vitro screening. To judge perfectly on their toxicity, in-vitro screening must compared to positive control as Doxorubicin (reference drug). IC50 values were calculated and represent Cu(II) complexes as outstanding cytotoxic agents which revealed superiority on the reference drug itself.